Highly rigid rubber composition
The silica-filled rubber composition with polar functional groups at one end of hydrophobic carbon chains addresses the balance between rigidity and rolling resistance, enhancing tire performance by improving dispersion and reducing viscosity.
Patent Information
- Application Number
- JP2024545256
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-31
- Filing Date
- 2023-01-30
- Publication Date
- 2025-01-30
AI Technical Summary
Existing silica-filled rubber compositions for tires face a challenge in achieving a balance between rigidity and rolling resistance, as increasing rigidity often worsens hysteresis and rolling resistance, which is not acceptable in current tire industry standards.
A silica-filled rubber composition is developed with a compound containing polar functional groups and hydrophobic carbon chains, where the polar functional group is located at one end of the hydrophobic carbon chain, enhancing silica dispersion and reducing viscosity, thereby improving rigidity while maintaining acceptable rolling resistance.
The composition achieves an optimal balance between rigidity and rolling resistance, with a bipolar moment higher than 3.5, ensuring improved handling performance and reduced hysteresis.
Smart Images

Figure 2025503299000001 
Figure 2025503299000002 
Figure 2025503299000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a silica-filled rubber composition for tires having high stiffness, a tire tread comprising said silica-filled rubber composition, and a tire comprising said tire tread, the silica-filled rubber composition comprising a compound having a dipole moment higher than at least 2 Debye, the compound comprising one or more polar functional groups and a hydrophobic carbon chain, the one or more polar functional groups being located at only one end of the hydrophobic carbon chain. [Background technology]
[0002] In the tire industry, manufacturers have expressed a need for rubber compositions that allow the production of tire components with low hysteresis and therefore low rolling resistance. In this regard, those skilled in the art have implemented advantageous solutions to better disperse fillers in the rubber compositions from which tire components are made. Such solutions include, for example, using functionalized polymers or functionalized fillers, or optimizing the mixing process of the rubber composition.
[0003] While such a solution can ensure a low level of hysteresis, it has the drawback of reducing the stiffness of the rubber composition, which, as known to those skilled in the art, results in poor handling properties.
[0004] Solutions that increase the stiffness of the composition generally increase the hysteresis and worsen the rolling resistance of the composition, which is unacceptable by current tire industry standards.
[0005] In the rubber compounding industry, "additives" are materials such as processing aids, fillers, curatives, etc., that are added to the rubber matrix in specific proportions to provide a homogeneous mixture that has the desired physical and chemical properties to meet required performance requirements.
[0006] As known to those skilled in the art, the addition of fillers such as silica to rubber tire compositions in the absence of other specific additives increases stiffness and also rolling resistance. This is because, in the absence of other specific additives, silica generally has poor dispersion due to its immiscibility in the rubber matrix. Poor dispersion of silica directly affects the increase in hysteresis and the deterioration of rolling resistance of the composition.
[0007] For this reason, plasticizers are added to silica-filled rubber compositions to reduce the viscosity of the composition, thereby improving the dispersibility of the silica and the mixability of the composition.
[0008] Compounds having polar functional groups and hydrophobic carbon chains can be used as plasticizers for silica-filled rubber compositions, where the compound can interact with the silica due to the presence of the polar functional groups, and at the same time disperse the silica attracted to the polar functional groups in the polymer matrix due to the presence of the hydrophobic carbon chains.
[0009] Thus, the addition of plasticizers favors optimal hysteresis obtained by process means, but this increased dispersion comes at the expense of poorer stiffness properties. Summary of the Invention [Problem to be solved by the invention]
[0010] Therefore, there is a need to find a solution that provides silica-filled rubber compositions with improved stiffness while maintaining acceptable rolling resistance values.
[0011] The present inventors have discovered that the polarity and chemical structure of the plasticizer added to a silica-filled rubber composition can provide an optimal balance between the stiffness and hysteresis of the composition. [Means for solving the problem]
[0012] In a first aspect, the present invention relates to a rubber composition comprising a crosslinkable polymer base, a filler comprising silica, and a vulcanization system, further comprising a compound having a dipole moment higher than at least 2 Debye, the dipole moment being calculated by a density functional theory (DFT) simulation, characterized in that said compound comprises one or more polar functional groups and a hydrophobic carbon chain, the polar functional group being located at only one end of the hydrophobic carbon chain.
[0013] In a second aspect, the present invention relates to a tire tread comprising the rubber composition of the first aspect.
[0014] In a third aspect, the present invention relates to a tire comprising a tread according to the second aspect.
[0015] Preferred features of the invention are the subject of the dependent claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] In a first aspect, the present invention relates to a rubber composition comprising a crosslinkable polymer base, a filler comprising silica, and a vulcanization system, further comprising a compound having a dipole moment higher than at least 2 Debye, the dipole moment being calculated by DFT simulation, said compound comprising one or more polar functional groups and a hydrophobic carbon chain, the polar functional group being located at only one end of the hydrophobic carbon chain.
[0017] In the following, the term "crosslinkable polymer base" means any natural or synthetic non-crosslinked elastomer that can assume all of the typical chemical, physical and mechanical properties of elastomers by crosslinking (vulcanizing) them with a sulfur system.
[0018] Non-limiting examples of elastomers suitable for use in the crosslinkable polymer base include, but are not limited to, styrene-butadiene rubber (also known as SBR or styrene-butadiene copolymer), polybutadiene (also known as BR), natural rubber (also known as NR), ethylene propylene diene monomer rubber (also known as EPDM rubber), butyl rubber (also known as IIR), polyisobutylene rubber, epoxidized natural rubber (also known as ENR), neoprene, synthetic polyisoprene (also known as IR), polyurethane (also known as PU), and the like.
[0019] The elastomers used in the crosslinkable polymer base may include functionalized elastomers.
[0020] The term "functionalized elastomer" should be interpreted to include elastomers having functional groups at one or both ends of the elastomer chain, or in the backbone of the elastomer, and any combination thereof. For example, a silica-reactive functionalized elastomer can have functional groups at one or both ends of the chain, or in the backbone, or both.
[0021] Non-limiting examples of silica-reactive functional groups known for use in functionalizing elastomers and suitable for use in the crosslinkable polymer base include nitrogen-containing functional groups, silicon-containing functional groups, oxygen- or sulfur-containing functional groups, metal-containing functional groups, and the like.
[0022] The elastomer used in the crosslinkable polymer base is preferably selected from polybutadiene (BR), styrene-butadiene copolymer (SBR), natural rubber (NR), or a mixture of these three. More preferably, the elastomer used in the crosslinkable polymer base is selected from styrene-butadiene copolymer (SBR), natural rubber (NR), or a mixture of these two. In particular, the crosslinkable polymer base can be a mixture containing 50-100 phr SBR and 0-50 phr NR, preferably 60-90 phr SBR and 10-40 phr NR, more preferably 65-85 phr SBR and 15-35 phr NR.
[0023] The term "natural rubber" refers to naturally occurring 1,4-cis polyisoprene polymer that can be obtained, for example, from Hevea rubber trees and non-Hevea sources (e.g., guayule shrub and dandelion such as TKS).
[0024] The rubber composition includes a filler. The filler includes silica. In a specific embodiment, the rubber composition includes 60 to 120 phr of silica, preferably 70 to 110 phr of silica, and more preferably 80 to 100 phr of silica.
[0025] In certain embodiments, one or more silane coupling agents may be used in combination with the silica to improve its dispersibility. According to certain embodiments, the amount of silane coupling agent is 0.01-40% by weight, preferably 0.01-30% by weight, more preferably 0.01-25% by weight, and even more preferably 0.01-10% by weight, based on the silica. In general, any conventional type of silane coupling agent may be used, such as those having a silicon group and a site capable of reacting with rubber, particularly vulcanizable rubber. The silane coupling agent acts as a linking bridge between the silica and the rubber. Examples of suitable silane coupling agents include those containing groups such as mercapto, blocked mercapto, polysulfide, amino, vinyl, epoxy, and combinations thereof. Preferably, the silane used in the present invention is bis[(triethoxysilyl)propyl]polysulfide (Si69).
[0026] The filler may further include any additional filler selected from carbon black, graphite, graphene, carbon nanotubes, recycled carbon black, clay, titanium dioxide, magnesium dioxide, aluminum oxide, starch, boron nitride, silicon nitride, aluminum nitride, calcium silicate, silicon carbide, or mixtures thereof.
[0027] The rubber composition further comprises a vulcanization system. In this specification, the term "vulcanization system" refers to compounds capable of inducing crosslinking of a polymer base, such as sulfur and accelerators. In general, the vulcanization system comprises at least one of a vulcanization agent, a vulcanization accelerator, a vulcanization activator (e.g., zinc oxide, stearic acid, etc.), a vulcanization inhibitor, and a scorch inhibitor. The curing package that can be used in the present invention comprises at least one vulcanization agent, at least one vulcanization accelerator, and optionally a vulcanization inhibitor and / or a scorch inhibitor. The vulcanization accelerator and the vulcanization activator act as catalysts for the vulcanization agent. The vulcanization inhibitor and the scorch inhibitor are known in the art and can be selected by a person skilled in the art based on the desired vulcanization properties.
[0028] Examples of types of vulcanizing agents suitable for use in rubber coatings include, but are not limited to, sulfur-based curing components or peroxide-based curing components. Examples of suitable sulfur-based vulcanizing agents include soluble sulfur, such as amine disulfide, sulfur donor curing agents such as polymeric polysulfides or sulfur olefin adducts, and insoluble polymeric sulfur. Each vulcanizing agent can be used alone or in combination. Preferably, the sulfur-based vulcanizing agent is insoluble sulfur or a mixture of soluble and insoluble polymeric sulfur. Typically, the vulcanizing agent is used in an amount ranging from 0.1 to 5 phr, preferably 1 to 3 phr.
[0029] Accelerators are used to control the time and / or temperature required for vulcanization and improve the properties of the vulcanizate. Examples of vulcanization accelerators suitable for use in the rubber coating of the present invention include, but are not limited to, thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, 2,2'-dithiobis(benzothiazole) (MBTS), sulfonamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide (TBBS), N,N-dicyclohexyl-2-benzothiazole sulfenamide (DCBS), guanidine-based vulcanization accelerators such as diphenylguanidine (DPG), thiuram-based vulcanization accelerators such as tetrabenzylthiuram disulfide (TBzTD), carbamate-based vulcanization accelerators, hexamethylene-1,6-bisthiosulfate (HTS), and the like. Preferably, the vulcanization accelerator used in the present invention is CBS, MBTS, DPG, or a mixture of the three. Usually, the vulcanization accelerator is used in an amount ranging from 0.1 to 10 phr, preferably from 0.5 to 5 phr.
[0030] Vulcanization accelerators are used as additives to assist vulcanization. Generally, vulcanization activators are classified into inorganic and organic components. Zinc oxide is the most widely used inorganic vulcanization activator. Various organic vulcanization activators are widely used, such as stearic acid, palmitic acid, lauric acid, and zinc salts thereof. Usually, the vulcanization activator is used in an amount ranging from 0.1 to 8 phr, preferably from 0.5 to 5 phr.
[0031] Vulcanization inhibitors are used to control the vulcanization process, generally to delay or inhibit vulcanization until a desired time and / or temperature is reached. Common vulcanization inhibitors include, but are not limited to, PVI (cyclohexylthiophthalmide) and the like. Typically, vulcanization inhibitors are used in amounts ranging from 0.1 to 3 phr, preferably 0.5 to 2 phr.
[0032] The rubber composition further includes a compound having a dipole moment higher than at least 2 Debye, the compound including one or more polar functional groups and a hydrophobic carbon chain, the polar functional group being located at only one end of the hydrophobic carbon chain.
[0033] Preferably, the dipole moment of the compound is at least higher than 3.5 Debye.
[0034] It is understood that when positive and negative charges are present in a molecular structure at uneven concentrations, a dipole is generated in the molecule. The dipole arises from the difference in electronegativity of the atomic components. This is because in the molecular structure, some atoms have a higher electronegativity than others, which causes the atoms to pull the shared electron pairs more strongly, resulting in the separation of positive and negative charges along the molecular structure. Dipoles are usually generated due to the presence of electronegative heteroatoms such as oxygen and nitrogen in molecules composed of hydrophobic carbon skeletons. It can be seen that the greater the difference in electronegativity of the atomic components, the greater the dipole.
[0035] The magnitude of the dipole is expressed as the dipole moment (p). Therefore, the dipole moment of a molecule is a measure of the polarity of the molecule, and a molecule with a permanent dipole moment is called a polar molecule.
[0036] The dipole moment is calculated using the following formula:
number
[0037] In a preferred embodiment, the compound comprises one or more polar functional groups and a hydrophobic carbon chain, with the polar functional group being located at only one end of the carbon chain.
[0038] In a further preferred embodiment, the compound described above comprises at least two or more polar functional groups and a hydrophobic carbon chain, the two or more polar functional groups being located at only one end of the carbon chain.
[0039] As used herein, the term "polar functional group" refers to a substituent or moiety that confers polarity to a molecule and determines the molecule's characteristic chemical reactions and compatibility with other chemicals. Each functional group is classified as polar or non-polar depending on its atomic composition and organization. The term polar refers to a group that has a specific orientation and high electronegativity on a molecule, resulting in an unbalanced distribution of electrons and thus determining the charge on the entire molecule.
[0040] Examples of polar functional groups include oxygen-based polar functional groups such as hydroxyl groups, carbonyl groups, carboxyl groups, ester groups, and the like, or nitrogen-based polar functional groups such as amide groups, amino groups, and the like.
[0041] In a further preferred embodiment, the compound comprises at least one or more, preferably two or more, oxygen-based polar functional groups and a hydrophobic carbon chain, the two or more oxygen-based polar functional groups being located at only one end of the carbon chain.
[0042] In a more preferred embodiment, the hydrophobic chain is a linear hydrophobic carbon chain having 12 to 22 carbon atoms, preferably 14 to 20 carbon atoms, more preferably 16 to 18 carbon atoms, and even more preferably 17 carbon atoms.
[0043] As used herein, the term "linear hydrophobic carbon chain" means a straight chain, in which the carbon atoms may be fully saturated or may have double bonds along the chain, and in which the carbon atoms are interconnected. A straight carbon chain is distinguished from a branched carbon chain in which the carbon atoms bear carbon substituents (alkyl groups).
[0044] Suitable examples of compounds containing a linear hydrophobic carbon chain having 12 to 22 carbon atoms and two or more oxygen-based polar functional groups located at only one end of the carbon chain include polyols having two or more hydroxy groups located at one end of the chain, or polyhydric alcohol esters derived from alcohols in the ester group, the terminal hydrocarbon portion of which is a fatty acid containing two or more hydroxy groups.
[0045] Fatty acid esters (FAEs) are a type of ester formed by combining a fatty acid with an alcohol. When the alcohol is a polyhydric alcohol, the terminal hydrocarbon portion of the ester group derived from the alcohol will necessarily contain one or more hydroxy groups.
[0046] In a preferred embodiment, the compound is a polyhydric alcohol ester of a fatty acid having a linear hydrophobic carbon chain containing 12 to 22 carbon atoms, and the terminal hydrocarbon moiety derived from the alcohol of the ester functionality contains two or more terminal hydroxy groups.
[0047] In a preferred embodiment, the polyalcohol component of the FAE is glycerol. When the polyalcohol component of the FAE is glycerol, the fatty acid esters produced can be monoglycerides containing a single hydrocarbon chain, diglycerides containing two hydrocarbon chains, or triglycerides containing three hydrocarbon chains.
[0048] In a further preferred embodiment, said compound is a monoglyceride of a fatty acid, more particularly a monoglyceride of stearic acid.
[0049] In a preferred embodiment, the compound is contained in an amount ranging from 1 to 10 phr, preferably from 1.5 to 8.5 phr, more preferably from 3 to 7 phr, and further preferably from 4 to 6 phr, based on the composition.
[0050] In certain embodiments, the rubber composition may further include one or more additional ingredients.
[0051] The rubber composition may further include one or more process oils. Process oils are useful for reducing the Mooney viscosity of the rubber composition before curing to improve processability. In such embodiments, the one or more process oils may be added to the rubber composition as free oils, as part of one or more diene-based elastomers (i.e., as extender oils), or as a combination of both. Non-limiting examples of oils that may be used in the rubber composition include paraffinic, naphthenic, aromatic, and the like. Preferably, the oil used in the present invention is octyl oleate. The rubber composition may include 0 (any) to 30 phr of one or more oils (process, extender, or both), preferably 1 to 25 phr, preferably 1 to 15 phr, more preferably 1 to 10 phr of one or more oils as described above.
[0052] The rubber composition may further include other conventional rubber additives, such as, for example, antidegradants, such as antioxidants and antiozonants.
[0053] Antidegradants are ingredients added to protect rubber from oxidative attack. Examples of antidegradants include phenylenediamines (e.g., N-(1,3-dimethylbutyl)-N'-phenyl-1,4-benzenediamine (6PPD)), trimethyldihydroquinolines (e.g., 2,2,4-trimethyl-1-1,2-dihydroquinoline-containing compounds (TMQ)), phenols, alkylated diphenylamines (DPAs), paraffin waxes or microcrystalline waxes or blends thereof, aromatic phosphites, and diphenylamine-ketone condensates. The appropriate amount of such ingredients can be determined by one skilled in the art.
[0054] In certain embodiments, the rubber composition of the present invention has a ratio of elastic modulus (E') at 30°C to dielectric dissipation factor (TanD) at 60°C, measured according to ISO standard 4664, of at least 1.15 to obtain a desired balance of performance, stiffness, and rolling resistance.
[0055] The elastic modulus (E') of a rubber composition is a measure of the rubber's resistance to elastic deformation under load. A higher modulus value means a stiffer rubber composition.
[0056] The dielectric tangent (TanD) or loss factor of a rubber composition is a measure of hysteresis, the ratio of the loss modulus to the storage modulus, and represents the energy dissipation ability of a material. The lower the value of TanD at 60°C, the better the rolling resistance of the rubber composition.
[0057] In a preferred embodiment, the ratio of E' / TanD in the rubber composition is in the range of 1.17 to 1.25.
[0058] In a second aspect, the present invention relates to a tire tread comprising the rubber composition of the first aspect.
[0059] In a third aspect, the present invention relates to a tire comprising a tread according to the second aspect. EXAMPLES
[0060] The following examples illustrate specific and exemplary embodiments and / or features of the present invention. The examples are provided for illustrative purposes only and should not be construed as limitations of the present invention. Many variations on these specific examples are possible without departing from the scope of the present invention. More specifically, the elastomers and other components (e.g., curing package components, anti-degradants, or process oils, etc.) utilized in the following examples can be substituted with other or additional components consistent with the disclosure in the detailed description and should not be construed as limiting.
[0061] A blank composition (Blank), a set of inventive Example A (1-2), and two different sets of comparative examples B (1-2) and C (1-2) were prepared. The blank composition does not contain any additive that acts as a plasticizer for silica. Inventive Example A (1-2) contains different amounts of glycerol monostearate according to the following formula:
[0062] [ka] Here the dipole moment is 5 Debye.
[0063] Comparative Example B(1-2) contains a different amount of additive (Additive B), which is represented by the following formula: [ka] Here the dipole moment is 1.4 Debye.
[0064] Comparative Example C(1-2) contains different amounts of an additive (Additive C), which is a branched polyol according to the following formula (n=2): [ka] Here, the dipole moment is 3.4 Debye and it has polar functional groups at both ends of the branched carbon chain.
[0065] The dipole moments of glycerol monostearate and additive B were calculated using the density functional theory calculation method, applying the gradient-corrected exchange functional of Becke and the gradient-corrected correlation functional of Lee, Yang, and Parr, commonly known as the BLYP functional, as described in "Assessment of Conventional Density Functional Schemes for Computing the Dipole Moment and (Hyper)polarizabilities of Push-Pull π-Conjugated Systems (A 2000, 104, 20, 4755-4763)" published in J. Physical Chemistry. In particular, DFT simulations were performed using the OCRA code described in "The ORCA program system (Wiley interdisciplinary Reviews - Computational Molecular Science, 2012, Vol 2., Issue 1, Pages 73-78.)".
[0066] The rubber compositions of all the examples (blank, inventive examples, and comparative examples) were prepared according to the formulations shown in Tables 1 and 2, with all components listed in phr.
[0067] [Table 1]
[0068] [Table 2]
[0069] The average molecular weight of the SBR used is 300-2000 kDa and the styrene content is 20-40%.
[0070] The silica used is sold under the name ULTRASIL VN3 by the company DEGUSSA.
[0071] The silane coupling agent used was bis[3-(triethoxysilyl)propyl]polysulfide silane (Si69).
[0072] The oil used was octyl oleate.
[0073] DPG is an abbreviation for diphenyl-guanidine, a compound used as a vulcanization accelerator.
[0074] MBTS is an abbreviation for mercaptobenzothiazole disulfide, which was used as a vulcanization accelerator.
[0075] CBS is an abbreviation for the compound N-Cyclohexyl-2-benzothiazolesulfenamide, which was used as a vulcanization accelerator.
[0076] (Sample preparation) All example rubber compositions in Table 1 were mixed according to the following mixing procedure. The crosslinkable polymer base and carbon black were charged into a mixer having a tangential rotor and an internal volume of 230 to 270 liters, and mixing was then started to give a filling rate of 66 to 72%.
[0077] (First mixing step) The mixer was operated at a speed ranging from 40 to 60 revolutions per minute, and the resulting mixture was discharged after the temperature reached a range of 140 to 160°C.
[0078] (Second mixing step) The mixture obtained in the previous step was freshly processed in a mixer operating at a speed in the range of 40-60 revolutions per minute and then removed after the temperature reached a range of 130-150°C.
[0079] (Final Mixing Step) A vulcanization system (sulfur, accelerators, anti-reversion agents, antioxidants / antiozonants, zinc oxide) was added to the mixture obtained in the previous step to achieve a loading of 63-67%.
[0080] Mixing was performed at 20-40 revolutions per minute, and the resulting mixture was discharged after the temperature reached a range of 100-110°C.
[0081] Each of the compositions set forth in Tables 1 and 2 was vulcanized and comparative vulcanized samples were tested according to IOS Standard 4664 to evaluate the elastic modulus E' (30°C) and Tan D (60°C).
[0082] Tables 3 and 4 below report the values of modulus E'(30°C) and TanD(60°C) measured on samples obtained from the above compositions. These values were indexed to composition B-1, which contains 2 phr of additive B, which represents the common practice for the application of silica plasticizers in rubber compounding technology. It can be seen that the lower the TanD(60°C) value, the lower the rolling resistance, so a lower TanD is preferred, and the higher the E'(30°C) value, the higher the stiffness, so a higher E' is the preferred property. It is considered that E' / TanD is greater than or equal to 1.15, preferably between 1.17 and 1.25.
[0083] [Table 3]
[0084] [Table 4]
[0085] From the above data, it is clear that the use of the additive according to the invention (additive A) allows the stiffness of the compound to be increased while at the same time maintaining a reasonable or even lower value of rolling resistance, resulting in an E' / TanD ratio of more than 1.15, thus obtaining an optimal balance between the two properties. In contrast, the use of additive B, which is less polar than glycerol monostearate, results in good rolling resistance but at the expense of stiffness, resulting in an E' / TanD ratio closer to 1, while the use of additive C, which has polar groups at both ends of a branched hydrophobic carbon chain, results in a poor balance between the two properties, resulting in an E' / TanD ratio of less than 1.15, due to low stiffness and high rolling resistance compared to the case with glycerol monostearate added.
[0086] This data confirms that plasticizers with polarity below a certain level facilitate dispersion of the silica in the polymer matrix via hydrophobic carbon chains and reduce the viscosity of the composition, resulting in good hysteresis but with a trade-off in stiffness.
[0087] On the other hand, the plasticizers according to the present invention, which have polarity above a certain level and in which the polar functional group is located at only one end of the carbon chain, can directly and efficiently interact with the silica by bonding directly to it, providing good hysteresis while still favoring the dispersion of the silica in the polymer matrix due to the hydrophobic carbon chain, and at the same time ensuring good stiffness levels.
Claims
1. A rubber composition comprising a crosslinkable polymer base, a filler comprising silica, and a vulcanization system, further comprising a compound having a dipole moment higher than at least 2 Debye, said dipole moment being calculated by DFT simulation, said compound comprising one or more polar functional groups and a hydrophobic carbon chain, said polar functional group being located at only one end of said hydrophobic carbon chain.
2. 10. The rubber composition of claim 1, wherein the compound has a dipole moment greater than at least 3.5 Debye.
3. 3. The rubber composition according to claim 1, wherein the compound comprises at least two of the polar functional groups and the hydrophobic carbon chain, and the polar functional group is located at only one end of the hydrophobic carbon chain.
4. The rubber composition according to any one of claims 1 to 3, wherein the one or more polar functional groups are oxygen-based polar functional groups.
5. The rubber composition according to any one of claims 1 to 4, wherein the hydrophobic carbon chain is a linear hydrophobic carbon chain having 12 to 22 carbon atoms.
6. 6. The rubber composition of claim 1, wherein the compound is a polyalcohol ester of a fatty acid having a linear, hydrophobic carbon chain containing from 12 to 22 carbon atoms, the alcohol-derived terminal hydrocarbon portion of the ester functionality containing at least two hydroxy end groups.
7. A rubber composition according to any one of the preceding claims, wherein the compound is a glycerol fatty acid ester, in particular a monoglyceride of a fatty acid, in particular a monoglyceride of stearic acid.
8. The rubber composition according to any one of claims 1 to 7, wherein the amount of the compound added to the rubber composition is in the range of 1 to 10 phr, preferably 1.5 to 8.5 phr, more preferably 3 to 7 phr.
9. A rubber composition according to any one of the preceding claims, wherein the rubber composition comprises from 60 to 120 phr of silica, preferably from 80 to 100 phr of silica.
10. The rubber composition according to any one of claims 1 to 9, further comprising a silane coupling agent.
11. The rubber composition according to any one of claims 1 to 10, wherein the crosslinkable polymer base comprises natural rubber and a butadiene copolymer, preferably a styrene-butadiene copolymer (SBR).
12. The rubber composition according to any one of claims 1 to 11, wherein the crosslinkable polymer base comprises 15 to 45 phr of natural rubber and 55 to 85 phr of styrene-butadiene copolymer, more preferably 25 to 35 phr of natural rubber and 65 to 75 phr of styrene-butadiene copolymer.
13. The rubber composition according to any one of claims 1 to 12, wherein the ratio (E' / TanD) of the elastic modulus E' at 30°C to the dielectric loss tangent TanD at 60°C of the rubber composition is 1.17 to 1.
25.
14. A tire tread made from the rubber composition of any one of claims 1 to 13.
15. A tire comprising the tire tread of claim 14.
Citation Information
Patent Citations
Special dispersing aid ZD-6 for white carbon black
CN104693486A
Rubber composition and pneumatic tire using the same
JP2014210829A
Rubber composition and pneumatic tire using the same
JP2016037601A
Additive composition for silica blended rubber composition, rubber composition and tire
JP2016160424A
Rubber composition and tire
JP2020132860A